(untitled) - Barry Hawkes (London, 1994)
This book presents a practical descriptive coverage of the principles, components and facilities of computer-aided design and manufacture processes and of their utilisation in the development of advanced manufeacturing systems. The treatment is particularly rich in real illustrative examples and case studies from all levels of production and manufacturing engineering. It is extensively illustrated with line drawings and photographs
Keywords: cad/cam systems,computer-aided engineering